REALISASI THE PUBLICNESS OF PUBLIC GOODS MELALUI SKEMA DESA WISATA - Karyaningtyas, Setyowati (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2025)
This study aims to describe the provision of The Publicness of Public Goods through a tourist village scheme. The study was conducted in the Sidomulyo tourist village, Silo District, Jember Regency, which is one of the remote villages at the tip of Jember Regency which is a village fostered by many parties with the highest stunting rate in Tapal Kuda (the name for the area at the eastern tip of East Java which includes Pasuruan, Probolinggo, Lumajang, Bondowoso, Situbondo, and Banyuwangi). Since the development of the tourist village initiated by the Silo Youth Movement in 2017, this village has been able to become an independent village and zero stunting in 2021. Not only that, GPS is also able to provide public goods that were previously unable to be provided by the government or other parties. This study uses a qualitative approach with a descriptive type conducted in Sidomulyo Village, Silo District, Jember Regency. There are two types of data used, namely primary data and secondary data. Primary data is obtained using in-depth interview techniques and non-participant observation, while secondary data is obtained using documentation techniques and literature studies. The results of data obtained from the field were then tested for validity through the source triangulation technique and analyzed using interactive data analysis methods. The results of the study showed that since the existence of a tourist village initiated by GPS, it has been able to provide goods needed by the Sidomulyo community consisting of the provision of tourist village infrastructure, tourist village amenities, and health services. This is in line with the 3A management in tourism, namely Attractions, Amenities and Accessibility, which are the three main aspects that are the basis for planning tourism development in a tourist destination.